Meningkatkan Kreativitas Anak Usia Dini melalui Metode Bermain dengan Permainan Balok di Taman Kanak-Kanak Negeri 2 Bukit Kapur Kota Dumai Tahun Pelajaran 2018/2019 - Dewi Herlina (Bedelau: Journal of Education and Learning, 2021)
Children are true learners who always want to know in realizing curiosity and expressing their feelings. All parents naturally want to make their children happy, seeing them grow up healthy, smart, and successful in their lives. Therefore, in order to educate children, they must use reliable strategies, such as using games. Playing in principle is the most influential factor in a child's self-development period, essentially playing is very closely related to children's development. Learning to play is expected to increase children's knowledge, creativity, and various aspects of children's development, especially cognitive intelligence on children's creativity. Therefore the implementation of pre-school children's education has been regulated in the National Education System Law by finding a new perspective on children's education, namely the concept of Early Childhood Education (PAUD) in 2003. The idea of ​​PAUD basically wants to sharpen the concept of pre-school children's education as an initial view according to the context of the times. Therefore, departing from children as an initial step to introduce education to early childhood, it is hoped that through block games can improve the development of children's creativity, especially in early childhood in Taman Kanak-kanak Negeri 2 Bukit Kapur Kota Dumai. So the authors raise the title of this study: Improving Early Childhood Creativity Through Playing Method with Beams in TK Negeri 2 Bukit Kapur, Dumai City, 2018/2019 Academic Year. This research is a field research, while the type of this research is action research that is focused in the arithmetic area or commonly referred to as Classroom Action Research (Classroom Action Research). In collecting the data needed the author uses data sources consisting of two sources, the first is the primary data source, the type of data taken from direct observation in class at B-1. Based on the results of data analysis, the results of this study can be shown by the authors there is an increase in each cycle, from cycle I, and cycle II. The authors conclude that the Method of Playing with Beam Games can enhance the Development of Creativity in children in the Taman Kanak- kanak Negeri 2 Bukit Kapur Kota Dumai.